ナンキョク ロケット S-210JA-21 ゴウキ ニヨル コウシュウハ プラズマ ハドウ スペクトル ノ カンソク e. イベント セッション ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 大家, 寛; オオヤ, ヒロシ; 宮岡, 宏; ミヤオカ, ヒロシ; 宮武, 貞夫; ミヤタケ, サダオ; OYA, Hiroshi; MIYAOKA, Hiroshi; MIYATAKE, Sadao (1980)
P(論文) 南極ロケットS-210JA-21号機に搭載されたPWHにより,南極域電離層における高周波帯プラズマ波動スペクトルの観測が行われた.その結果,ロケット近傍でのUHR周波数からZモードしゃ断局波数にかけての帯域,および電子サイクロトロン周波数以下,の2つの帯域において顕著なエミッションが観測された.前者のエミッションでは,その周波数変動が電離層電子密度の分布構造をよく反映しており,このエミッションが比較的ロケット近傍で励起されたものであることを示す.また後者のエミッションも同時に観測された降下電子フラックスと対応しており,これらのエミッションが極域電離層に降り込む降下粒子との波動粒子相互作用の結果,下部電離層レベルにおいて励起されたプラズマ波動であることが判明した. An observation of the plasma wave spectrum in a high frequency range from 0.1 to 10 MHz has been made using the ionospheric sounding rocket S-210JA-21, launched on July 26, 1976 from Syowa Station in Antarctica. Plasma wave emissions were observed in two frequency ranges the first range is from the UHR frequency to the Z-mode cut ofr frequency, and the second is a range lower than the electron cyclotron frequency. The center frequency of the first kind emissions indicates a variation corresponding to the local upper hybrid and to the electron plasma frequencies along the flight path of S-210JA-21, indicating an evidence that the emissions are produced in the ionosphere as a result of the wave-particle interaction due to the auroral precipitation particles. The intensity of the second type emissions has been changed in correlation with the electron flux in the 40-60 keV range that is observed by ESH simultaneously. It has been clarified that the second kind emissions are plasma waves of the electrostatic origin which are also excited at the lower ionospheric level by the electrons precipitating along the auroral field line. departmental bulletin paper